Activity based costing software for manufacturing industries - Shapi'i, Azrulhizam (2004)
Manufacturing companies in Malaysia face ever-increasing competition in today's global marketplace. Companies must react quickly and manufacture high quality, low cost products to be successful in this new environment. Nowadays, complexity-manufacturing technology has led to increasing indirect cost or overhead cost in the calculation of the total production cost. The failure of traditional costing method in tracing overhead cost to products has caused the distortion of product cost. A new costing method named Activity Based Costing (ABC) has been introduced as an alternative for solving the problem. This ABC method has been implemented for product costing. The main purpose for this study is to develop computerized ABC system for the manufacturing companies. This software enables the companies to identify the characteristics of activities and the costs involved in activities. ABC can assign dollar values to every activity or process. The ABC software is hoped to improve further the process planning and action of manufacturing companies through cost savings and improving revenue.